Defining digital humanities and examining its relationship with linguistics through the lens of Digital Scholarship in the Humanities. - Yan, Jianwei; Li, Qidi; Liu, Haitao (Digital Scholarship in the Humanities, 2025)
Digital humanities (DH) is an emerging interdisciplinary academic field that has gained prominence in recent decades. This study explores the evolution of topics, research impact, and attractiveness of DH through the lens of the journal Digital Scholarship in the Humanities (DSH), a leading platform for DH research, from 1986 to 2023 (in three phases: 1986–2003, 2004–2014, and 2015–2023). The study also examines the role of linguistic research in DH. The results reveal that: (1) the primary themes and trends in DH research have evolved from text encoding and analysis to critical studies of technology, infrastructure, and knowledge production; (2) the citation patterns demonstrate the growing influence and recognition of DH within the humanities and computer sciences; (3) European and North American scholars have dominated DH networks, but new centers and scholars are emerging in Asia, South America, and Oceania; and (4) linguistics-related publications have given less attention to specific linguistic features but have provided vital intellectual support for DH. This study provides a data-based perspective on the development and direction of DH, and demonstrates the value of linguistic methods for mapping scholarly fields over time. Based on these findings, suggestions are made for scholars interested in DH.